REMOTE WORK AND EMPLOYEE SATISFACTION: THE IMPLICATIONS OF THE VIRTUAL ENVIRONMENT ON WELL-BEING AND WORKPLACE EFFICIENCY (PANGEEA, 2025)
In the digital era, remote work has become an essential element of the modern workforce, bringing with it both challenges and opportunities for employees and employers. The paper "Remote Work and Employee Satisfaction: The Implications of the Virtual Environment on Well-being and Workplace Efficiency" explores the impact of this work mode on employee well-being and productivity, highlighting both the advantages and the aspects that require careful management to ensure optimal balance between professional and personal life.
Keywords: telecommuting; employee satisfaction; productivity; opportunities